Lethal Autonomous Weapons Systems: Morality, Obligations, and Responsibility in the Law of War - Crawford, Kelly L. (Tufts Archival Research Center, 2023)
Lethal Autonomous Weapons Systems (LAWS) are problematic for the current legal regime surrounding warfare. No matter the position you take on their efficacy or the morality of using artificial intelligence (AI) during the targeting cycle, both International Humanitarian Law (IHL) and the International Criminal Justice (ICJ) system do not emphatically address the prospect of a non-human system taking part in decision-making. This paper will first address if LAWS have moral agency and if they can carry out IHL obligations. Next, it will address the shortcomings of the current IHL regime and propose a new framework to accommodate LAWS. Then, it will dissect the prospect of prosecuting a war crime “committed” by an autonomous system and propose a new mode of liability to account for LAWS. Finally, it will address the pragmatic concerns of introducing LAWS onto the battlefield.; Submitted in partial fulfillment of the degree Master of Arts at the Fletcher School of Law and Diplomacy.; Submitted to the Fletcher School of Law and Diplomacy.